2023
DOI: 10.1097/md.0000000000032944
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of retrograde type A aortic dissection after thoracic endovascular aortic repair in patients with type B aortic dissection

Abstract: Background: Retrograde type A dissection (RTAD) is a devastating complication of thoracic endovascular repair (TEVAR) with low incidence but high mortality. The objective of this study is to report the incidence, mortality, potential risk factors, clinical manifestation and diagnostic modalities, and medical and surgical treatments. Methods: A systematic review and single-arm and two-arm meta-analyses evaluated all published reports of RTAD post-TEVAR through January 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 110 publications
(216 reference statements)
0
3
0
Order By: Relevance
“…The balloon dilation process following stent placement can also result in damage to the intima of the aorta, thereby exacerbating aortic inflammation and making it more susceptible to developing RTAD ( 10 ). Second, the choice of stent used during surgery is also an important contributing factor to the formation of RTAD ( 11 ). Typically, the selection of stent graft models is based on preoperative CTA and intraoperative imaging findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The balloon dilation process following stent placement can also result in damage to the intima of the aorta, thereby exacerbating aortic inflammation and making it more susceptible to developing RTAD ( 10 ). Second, the choice of stent used during surgery is also an important contributing factor to the formation of RTAD ( 11 ). Typically, the selection of stent graft models is based on preoperative CTA and intraoperative imaging findings.…”
Section: Discussionmentioning
confidence: 99%
“…For asymptomatic RTAD patients, upon reviewing CTA during follow-up, we observed that a considerable number of patients exhibited varying degrees of aortic atherosclerosis. This suggests that potential aortic pathology is also a significant factor in RTAD ( 11 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation